Ta’ṡīru Ansyiţati Al-muhādaṡati Al-usbūiyyati fĩ Kafāati Mahārati Al-kalām - Uswatun Hasanah; Intan Chumairo Nurwahidah (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
Speaking is a reciprocal conversation between two or more people, and also this Speaking method is one used in presenting Arabic through Arabic conversation. From that, the researchers wanted to know whether there was an influence from the weekly conversation activities, if any, how big the effect was on the conversation skills of the second semester B students of the Dirosat Islamiyah Al-Amien (IDIA) Institute. In this study, researchers used quantitative research methods consisting of two variables, namely the activities of muhadatsah usbu’iyah (Variable X) and the ability of conversation skills (Variable Y). Meanwhile, the respondents in this study were students of semester II B of the Intensive program. In this study, the main instrument that researchers used in data collection was a questionnaire, and the supporting instrument was a test. From the description above, it can be concluded that the results of data analysis using a simple Linear Regression formula can be seen the value of the output t value = 0.110 with an insignificant level of 0.914 > 0.05, it can be seen that there is no influence on the variable of muhadatsah usbu’ activity. iyah (X) on the ability variable of maharoh kalam (Y). After conducting research and calculating using the SPSS Version 22 program, a significant value was obtained 0.914 > 0.05 and based on the t value, it is known that t count is smaller than t table (0.110 < 1.711) so it can be concluded that the muhadatsah usbu’iyah activities provide influence on the ability of maharoh kalam.